Sex tourism in Rosana (SP) and the two circuits of the urban economy - Pimentel, Juliana Maria Vaz; Farias, João Paulo Block de; Buscioli, Roberson da Rocha; Denkewicz, Patricia (Seven Editora, 2023)
The present discussion intends to apprehend the structure that engenders sex tourism and its consequences on the two circuits of the urban economy in the municipality of Rosana (SP). In the months when fishing is open there is an expansion of the flow of tourists and call girls who, together, are responsible for articulating a complex network of sexual profitability that ends up boosting the local economy. For the effective development of the research and achievement of the results was used as a methodological procedure interviews conducted with the subjects who integrate the network of sexual profitability, tourists and call girls and the application of a questionnaire aimed at the subjects who integrate the upper marginal circuit of the urban economy, aiming to reiterate the importance of the lower circuit of the urban economy over the upper marginal circuit of the urban economy, thus boosting the local economy. The results show that in the low fishing season there is a decrease in consumption in the marginal circuit of the urban economy and the decline in the income of the subjects who make up the sexual profitability network, thus highlighting the relevance that the high fishing season exerts on the local economy through the central presence of the call girl and the tourist, as subjects that stimulate the mechanisms that engender sex tourism in the municipality of Rosana and the district of Primavera (SP). DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-165